Hubungan Tindakan Ekstraksi Vakum pada Persalinan dengan Kejadian Asfiksia Neonatorum di RSUD Dr. H. Moch. Ansari Saleh Banjarmasin Tahun 2017 - Aprilea, Noor Adha; Suhrawardi, Suhrawardi; Zakiah, Zakiah (JURNAL KEBIDANAN BESTARI, 2020)
Relationship to The Vacuum Extraction Action on Childbirth with The Events of asphyxia Neonatorum at Dr. H. Moch. Ansari Saleh Hospital in 2017: The cause of respiratory failure on neonatal asphyxia obstructed the blood flow into the uterus. The disruption of blood flow caused the lack of oxygen flow from the mother to the fetus caused by vacuum extraction. Data in 2015 and 2016 there is an increased case of vacuum extraction from 57 cases (1,5%) in 2015 to 78 cases (2,2%) in 2016, the incidence of neonatal asphyxia has risen in 2015 as 541 cases (18,8%) are being 924 cases(20,5%). The aim of research to analyze vacuum extraction in labor with neonatal asphyxia in Dr. H. Moch. Ansari Saleh Banjarmasin Hospital in 2017. The method of research using an analytic survey has been done which cross-sectional analytic. The sample was neonatal asphyxia in Dr. H. Moch. Ansari Saleh Banjarmasin Hospital in 2017 was 319 neonatal and control sample was neonatal without neonatal asphyxia incidence were 638 neonatal by ratio 1:2. The samples were to be taken by proportional random sampling. The instrument of research was used by the neonatal cohort and mother's cohort in 2017. Data Analysis using Chi-square with the confidence interval, α = 0,005. The results of the research were of 957 respondents consisting of 319 infants (33,3%) neonatal asphyxia, and 61 neonatal (6,4%) used vacuum extraction. Bivariate analysis results found correlation between vacuum extraction in labor and neonatal asphyxia, ρ value ( 0,000)< α (0,05) and OR value = 6,385. The result of the research shows a vacuum extraction that can lead to neonatal asphyxia in Dr. H. Moch. Ansari Saleh Banjarmasin Hospital in 2017. Keyword: Neonatal Asphyxia, Vacuum Extraction